Reasons Given by ECEC Professionals for (Not) Being in Contact With Parents During the COVID-19 Pandemic - Hemmerich, Fabian; Erdem-Möbius, Hande; Burghardt, Lars; Anders, Yvonne (Frontiers in Psychology, 2021)
In response to the COVID-19 pandemic, the German government took drastic measures and imposed the temporary closure of early childhood education and care services (apart from emergency care). Most pedagogical professionals in ECEC settings were unable to provide institutional care for children during this period, and thus had difficulties fulfilling their legally mandated professional obligation to educate children. Building on the importance of professional-parent collaboration, this study investigates the reasons ECEC professionals gave for (not) being in contact with parents during this time. The database comprises a nationwide survey, conducted between April and May 2020 (n = 2,560 ECEC professionals). Results show that the vast majority of respondents were in contact with parents; their stated motives included providing informational or emotional support of parents and children, maintaining a relationship, or inquiring about family wellbeing. If they were not in contact with parents, the explanations included already existing contacts with parents by another member of the ECEC staff, an employer-mandated contact ban, problems from the parents’ side, or personal reasons. We find some differences between managers in center-based childcare, pedagogical employees in center-based childcare, and professionals in family-based childcare. Practical implications concerning professional-parent collaboration and the temporary closure of ECEC services are discussed.